Lighting and Marking of Agricultural Equipment on Highways: Summary of ASAE Standard S279.18 - Serap Gorucu; Charles Brown; Carol Lehtola (EDIS)
Agricultural vehicles on public roads can pose risks to their drivers and to drivers of other vehicles. Proper lighting and marking increase visibility of the farm equipment. This 6-page publication summarizes agricultural equipment lighting and marking standards. Written by Serap Gorucu, Charles Brown, and Carol Lehtola, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised February 2021.